$A) A_{ij} = (–1)^{i+j} M_{ij}$

$B) A_{ij} = 1^{i+j} M_{ij}$

$C) A_{ij} = (–1)^{i-j} M_{ij}$

$D) A_{ij} = 1^{i-j} M_{ij}$

$A) A_{ij} = (–1)^{i+j} M_{ij}$

$B) A_{ij} = 1^{i+j} M_{ij}$

$C) A_{ij} = (–1)^{i-j} M_{ij}$

$D) A_{ij} = 1^{i-j} M_{ij}$

$B) A_{ij} = 1^{i+j} M_{ij}$

$C) A_{ij} = (–1)^{i-j} M_{ij}$

$D) A_{ij} = 1^{i-j} M_{ij}$

related to an answer for:
If the Minor of an element $a_{ij}$ is denoted by $M_{ij}$ and the cofactor of an element $a_{ij}$ is denoted by $A_{ij}$ then, which of the following is true?

Ask Question

Tag:MathPhyChemBioOther

Take Test

...